Assembly factor for spindle microtubules (ASPM) promotes osimertinib resistance in lung cancer by increasing EGFR stability - Gui, Pengpeng; Han, Zhengyi; Yin, Zhenyu; Cao, Peng; Zhou, Xin; Li, Yan (Frontiers in Genetics, 2025)
BackgroundNon-small cell lung cancer (NSCLC) represents approximately 85% of all lung malignancies, with lung adenocarcinoma (LUAD) being the predominant histologic subtype. Epidermal growth factor receptor (EGFR) mutations serve as critical therapeutic targets in NSCLC; however, resistance to EGFR tyrosine kinase inhibitors (EGFR-TKIs) remains a major clinical challenge. Recent studies highlight the need to identify molecular drivers of resistance to improve therapeutic outcomes.MethodThis study analyzed tumor tissue datasets to investigate the role of the assembly factor for spindle microtubules (ASPM) in NSCLC progression and drug resistance. Bioinformatics methods revealed high expression of ASPM in tumor tissues and its association with low patient survival. Functional validation was performed using the EGFR-TKI-resistant cell line PC9 osimertinib-resistant (PC-9 OR), with ASPM-silenced models. Cellular proliferation, invasion, and EGFR protein stability analyses were conducted. Additionally, the therapeutic impact of ASPM silencing and overexpression combined with the third-generation TKI osimertinib was evaluated.ResultsASPM is significantly upregulated in NSCLC tumor tissues and is strongly associated with reduced patient survival. ASPM silencing attenuates PC-9 and PC-9 OR malignant phenotypes, including proliferation and invasion, and sensitizes resistant cells to osimertinib. In addition, inhibiting the expression of ASPM effectively reduces damage to the cell cycle and protein stability of drug-resistant cells, thereby restoring the expression and function of EGFR.ConclusionThis study identified ASPM as a novel regulator of EGFR-TKI resistance in NSCLC, with dual roles in promoting tumor aggressiveness and stabilizing EGFR signaling. Targeting ASPM may represent a promising therapeutic strategy to overcome EGFR-TKI resistance, enhance osimertinib efficacy, and expand treatment options for refractory NSCLC patients. These findings provide a foundation for developing ASPM-directed therapies in precision oncology.